Chidamide plus prednisone, etoposide, and thalidomide for untreated angioimmunoblastic T‐cell lymphoma in a Chinese population: A multicenter phase II trial. Issue 5 (11th March 2022) - Wang, Yawen; Zhang, Mingzhi; Song, Wei; Cai, Qingqing; Zhang, Liling; Sun, Xiuhua; Zou, Liqun; Zhang, Huilai; Wang, Lili; Xue, Hongwei
Abstract: Angioimmunoblastic T‐cell lymphoma (AITL) is a common type of peripheral T‐cell lymphoma (PTCL) with a poor prognosis, and an effective first‐line therapy is lacking. Chidamide is a selective histone deacetylase inhibitor and has been approved by the China Food and Drug Administration for relapsed or refractory PTCL. We conducted a multicenter phase II clinical trial combining chidamide with prednisone, etoposide, and thalidomide (CPET regimen) for a total of eight cycles in untreated AITL patients in China. The primary objectives were the overall response rate (ORR) and complete remission (CR) rate after eight cycles of the CPET regimen. The secondary endpoints were progression‐free survival (PFS) and safety. Of the 71 enrolled patients, 51 completed the eight cycles of the CPET regimen. The ORR and CR of the 51 patients were 90.2 and 54.9%, respectively. After a median follow‐up of 11.4 months (95% confidence interval [CI], 9.9–17.0), the median PFS of the 51 patients was 42.6 months (95% CI, 27.7—not reached) and the median overall survival (OS) was not reached. The 2‐year PFS rate and OS rate were 66.5 and 82.2%, respectively. Sixty‐eight patients received at least one cycle of CPET regimen and were included as the safety assessment population. The most common grade 3/4 adverse event was neutropenia ( n = 22, 32.3%). Twelve patients showed treatment‐related infections and recovered from antibiotic therapy; the other adverse events were mostly mild and reversible. The oral CPET regimen is an effective, tolerable, and economical choice for untreated AITL in a Chinese population. This trial was registered in www.clinicaltrials.gov as NCT03273452.